Winter report, Cedar Rapids area - Serbousek, Lillianet al (1977)
Winter report of bird sightings in the Cedar Rapids area, submitted by Lillian Serbousek. The following sightings are underlined: Saw-Whet Owls, Northern Shrike, Hoary Redpoll, and Pine Grosbeak. This item was used as supporting documentation for the Iowa Ornithologists Union Quarterly field report of winter, 1977-1978. Epson - sheet feed/flatbed